Continuous trench, pulsed laser ablation for micro-machining applications. (August 2016) - Cadot, G.B.J.; Axinte, D.A.; Billingham, J.
Abstract: The generation of controlled 3D micro-features by pulsed laser ablation in various materials requires an understanding of the material's temporal and energetic response to the laser beam. The key enabler of pulsed laser ablation for micro-machining is the prediction of the removal rate of the target material, thus allowing real-life machining to be simulated mathematically. Usually, the modelling of micro-machining by pulsed laser ablation is done using a pulse-by-pulse evaluation of the surface modification, which could lead to inaccuracies when pulses overlap. To address these issues, a novel continuous evaluation of the surface modification that use trenches as a basic feature is presented in this paper. The work investigates the accuracy of this innovative continuous modelling framework for micro-machining tasks on several materials. The model is calibrated using a very limited number of trenches produced for a range of powers and feed speeds; it is then able to predict the change in topography with a size comparable to the laser beam spot that arises from essentially arbitrary toolpaths. The validity of the model has been proven by being able to predict the surface obtained from single trenches with constant feed speed, single trenches with variable feed speed and overlapped trenches with constant feed speed for three different materials (graphite, polycrystalline diamond and a metal-matrix diamond CMX850) with low error. For the three materials tested, it is found that the average error in the model prediction for a single trench at constant feed speed is lower than 5 % and for overlapped trenches the error is always lower than 10 %. This innovative modelling framework opens avenues to: (i) generate in a repeatable and predictable manner any desired workpiece micro-topography; (ii) understand the pulsed laser ablation machining process, in respect of the geometry of the trench produced, therefore improving the geometry of the resulting parts; (iii) enable numerical optimisation for the beam path, thus supporting the development of accurate and flexible computer assisted machining software for pulsed laser ablation micro-machining applications. Abstract : Highlights: Continuous modelling of pulsed laser machining using trenches as a basis for the calibration of the model. Modelling framework is calibrated using a limited amount of experimental trials for any material and machining system. Accurate Prediction of the profile and depth of the trenches for a wide range of kinematic and energetic conditions for 3 materials. Accurate prediction of the profile and depth of overlapped trenches for 3 materials.